New application for TiO2 P25 photocatalyst: A case study of photoelectrochemical sensing of nitrite ions. (April 2021) - Mokhtar, Bassam; Kandiel, Tarek A.; Ahmed, Amira Y.; Komy, Zanaty R.
Abstract: Developing photoelectrochemical (PEC) sensors based on photocatalytic materials has recently attracted great interest as an emerging technology for environmental monitoring. TiO2 P25 is a well-known highly active photocatalyst, cheap, and produced commercially on a large scale. In the current work, a practical and durable TiO2 -based PEC sensor has been fabricated by immobilizing TiO2 P25 nanoparticles at disposable screen-printed carbon substrates using drop-casting method. The fabricated PEC sensor has been applied for the anodic-detection and determination of nitrite (NO2 − ) ions under UV(A) light (LED, 365 nm) using chronoamperometry (CA) and differential pulse voltammetry (DPV). Linear calibration curves were obtained between the photocurrent responses and the concentrations of NO2 −  ions in the ranges of 0.1–5.0 and 0.5–10 mg L −1  for CA and DPV, respectively. Surprisingly, the detection limits (sensitivities) of the fabricated sensor towards NO2 − ions under light were enhanced by a factor of 4.75 (4.1) and 8.3 (37.4) for CA and DPV, respectively, in comparsion with those measured in the dark. It is found that the photo-excitation of TiO2 facilitates the photooxidation of NO2 − ions via the photo-generated holes whereas the photogenerated electrons contribute to the enhanced photocurrent and consequently the enhanced detection limit and sensitivity. The fabricated TiO2 -based PEC sensor exhibits a good stability, durability, and satisfying selectivity for NO2 − ions determination. These results indicate that the TiO2 -based PEC sensor fabricated by utilizing cheap and commercially available components has great potential for being transferred from lab-to-factory. Graphical abstract: Image 1 Highlights: A sensitive and durable TiO2 -based photoelectrochemical (PEC) sensor has been fabricated. The fabricated PEC sensor exhibits high sensitivity and selectivity towards nitrite ions. Under UV(A) light, the detection limit was improved by 8.3-fold relative to that of the dark. The photo-sensitivity was increased by 37.4-fold relative to that of the dark. The fabricated sensor exhibits great potential for transfer from lab-to-factory.